ResolanaPaving Paths Toward Transformation with Incarcerated Women - Carolyn L. Sandoval; Lisa M. Baumgartner (Adult Education Research Conference, 2015)
The purpose of this study was to elicit the experiences of women who participated in a gender-responsive program in jail. Results indicate the holistic programming and learning environment was an emancipatory container where transformation could occur through interpersonal and intrapersonal engagement. Findings have implications for the education of incarcerated women.